Programmatic Management of Drug-Resistant Tuberculosis: An Updated Research Agenda - Mitnick, Carole D.; Rodriguez, Carly A.; Hatton, Marita L.; Brigden, Grania; Cobelens, Frank; Grobusch, Martin P.; Horsburgh, Robert; Lange, Christoph; Lienhardt, Christian; Oren, Eyal; Podewils, Laura J.; Seaworth, Barbara; et al. (PloS one, 2016)
There are numerous challenges in delivering appropriate treatment for multidrug-resistant tuberculosis (MDR-TB) and the evidence base to guide those practices remains limited. We present the third updated Research Agenda for the programmatic management of drug-resistant TB (PMDT), assembled through a literature review and survey. Publications citing the 2008 research agenda and normative documents were reviewed for evidence gaps. Gaps were formulated into questions and grouped as in the 2008 research agenda: Laboratory Support, Treatment Strategy, Programmatically Relevant Research, Epidemiology, and Management of Contacts. A survey was distributed through snowball sampling to identify research priorities. Respondent priority rankings were scored and summarized by mean. Sensitivity analyses explored weighting and handling of missing rankings. Thirty normative documents and publications were reviewed for stated research needs; these were collapsed into 56 research questions across 5 categories. Of more than 500 survey recipients, 133 ranked priorities within at least one category. Priorities within categories included new diagnostics and their effect on improving treatment outcomes, improved diagnosis of paucibacillary and extra pulmonary TB, and development of shorter, effective regimens. Interruption of nosocomial transmission and treatment for latent TB infection in contacts of known MDR-TB patients were also top priorities in their respective categories. Results were internally consistent and robust. Priorities retained from the 2008 research agenda include shorter MDR-TB regimens and averting transmission. Limitations of recent advances were implied in the continued quest for: shorter regimens containing new drugs, rapid diagnostics that improve treatment outcomes, and improved methods of estimating burden without representative data. There is continuity around the priorities for research in PMDT. Coordinated efforts to address questions regarding shorter treatment regimens, knowledge of disease burden without representative data, and treatment for LTBI in contacts of known DR-TB patients are essential to stem the epidemic of TB, including DR-TB.